RESTORASI LAHAN RAWA GAMBUT MELALUI METODE REWETTING DAN PALUDIKULTUR - L. Budi Budi Triadi (Jurnal Sumber Daya Air)
In general, degradation on peatlands is mainly caused by excessive conversion and selection of commodities that cannot grow in wet condition. Conversion of peatlands and extreme canalization have become major threats to peatlands which leads to peat fire, subsidence, flooding, green house emission, as well as economic and social problems.